A Pilot and Feasibility Study to Evaluate Small and Large Bite Fascial Closure Techniques - Gates, Clint; Berg, Gina M; Vincent, Kyle; Acuna, David; Ali, Kamran (Kansas Journal of Medicine, 2021)
Introduction. Few randomized controlled studies have been conducted comparing a small to large fascial bite technique, yet recommendations have been made to standardize small bite closures. However, large scale randomized controlled trials require considerable effort and may benefit from a pilot study. Methods. This multi-center randomized controlled pilot study of adult patients undergoing median laparotomy incision investigated the feasibility of studying the outcomes between small and large surgical closure techniques. Results. Fifty of 100 planned patients consented, 32 patients completed surgery and 19 patients completed the one-year ultrasound. Enrollment was 2.7 versus 8 patients per month pre/post addition of study coordinator. Clinical results are summarized for feasibility demonstration purposes, but not analyzed for hypothesis testing. The total cost of the pilot study was 19,152.50 and took 22 months from first surgery to final one-year ultrasound. Conclusions. This feasibility assessment demonstrates the complexity of planning a large scale randomized trial evaluating small and large bite surgical closure technique. To expand this pilot study to a full scaled sample size study would require dedicated personnel and large grant funding.